Can diversity encourage entrepreneurship in transition economies? - Elena Nikolova (IZA World of Labor, 2017)
Entrepreneurship is an important lever for spurring transition in the economies of the former Soviet Union and Central and Eastern Europe. Utilizing diversity, in terms of religion or gender, can positively affect entrepreneurial development. Programs that encourage entrepreneurial initiatives (such as business start-ups) in culturally diverse localities should rank high on the policy agenda. Prompting women to start a business, along with female-friendly measures (including targeted legislation), can positively affect entrepreneurial behaviour and the performance of existing enterprises.
Keywords: L26; P31; Z12; 330; entrepreneurship; diversity; gender; transition